The weWomen and ourCircle Randomized Controlled Trial Protocol: A Web-based Intervention for Immigrant, Refugee and Indigenous Women with Intimate Partner Violence Experiences - Sabri, Bushra (Contemp Clin Trials, 2018)
Intimate partner violence (IPV), including homicides is a widespread and significant public health problem, disproportionately affecting immigrant, refugee and indigenous women in the United States (US). This paper describes the protocol of a randomized control trial testing the utility of administering culturally tailored versions of the danger assessment (DA, measure to assess risk of homicide, near lethality and potentially lethal injury by an intimate partner) along with culturally adapted versions of the safety planning (myPlan) intervention: a) weWomen (designed for immigrant and refugee women) and b) ourCircle (designed for indigenous women). Safety planning is tailored to women’s priorities, culture and levels of danger. Many abused women from immigrant, refugee and indigenous groups never access services because of factors such as stigma, and lack of knowledge of resources. Research is, therefore, needed to support interventions that are most effective and suited to the needs of abused women from these populations in the US. In this two-arm trial, 1250 women are being recruited and randomized to either the web-based weWomen or ourCircle intervention or a usual safety planning control website. Data on outcomes (i.e., safety, mental health and empowerment) are collected at baseline and at 3, 6, and 12 months post- baseline. It is anticipated that the findings will result in an evidence-based culturally tailored intervention for use by healthcare and domestic violence providers serving immigrant, refugee and indigenous survivors of IPV. The intervention may not only reduce risk for violence victimization, but also empower abused women and improve their mental health outcomes.